2000
DOI: 10.1108/07363760010335321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of assimilation on consumer susceptibility to interpersonal influence

Abstract: The impact of assimilation on a consumer's susceptibility to interpersonal influence is assessed in samples of first-generation Armenian and Chinese immigrants to the US. We find that: (a) Chinese immigrants are more susceptible to interpersonal influence than are Anglo-Americans who in turn are more susceptible to this influence than are Armenian immigrants, (b) Chinese immigrants are especially susceptible to the normative type of interpersonal influence and (c) Chinese immigrants' susceptibility to both typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 16 publications
(20 reference statements)
1
23
0
1
Order By: Relevance
“…Also, the acculturation scale was found to have good internal consistency reliability based on a coefficient alpha of .7627, given that values of coefficient alpha above .60 are considered satisfactory (Peterson, 1994). The items in the scale were divided into three categories based on the type of assimilation: identification, integration, and acculturation according to definitions provided in previous studies (see D'Rozario and Choudhury, 2000;Gordon, 1964). The three scales were checked for internal consistency reliability using coefficient alpha.…”
Section: Level Of Acculturationmentioning
confidence: 99%
“…Also, the acculturation scale was found to have good internal consistency reliability based on a coefficient alpha of .7627, given that values of coefficient alpha above .60 are considered satisfactory (Peterson, 1994). The items in the scale were divided into three categories based on the type of assimilation: identification, integration, and acculturation according to definitions provided in previous studies (see D'Rozario and Choudhury, 2000;Gordon, 1964). The three scales were checked for internal consistency reliability using coefficient alpha.…”
Section: Level Of Acculturationmentioning
confidence: 99%
“…Subsequent research in consumer behaviour subdivided normative influence into value expressive and utilitarian influences 25,26 . Value expressive influence is generally defined as adopting the behaviour or opinions of another because of a satisfying self‐defining relationship with a group or individual 12,20,26 . Utilitarian influence is an individual's tendency to comply with the expectations of others to avoid punishment or to receive rewards 24 .…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Fundamentally, a high SUSCEP score indicates a tendency to be influenced by others in making decisions, while a low SUSCEP score indicates more independence in decision making 27 . Several researchers have used the SUSCEP scale successfully (for example 20,27,28 ). D’Rozario and Choudhury 20 concluded that consumer susceptibility to interpersonal influence varies with the level of assimilation into one's host culture and is therefore not a stable trait as was assumed in the previous literature.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…In academia, recent studies have examined the distinct characteristics and consumption patterns of ethnic minority populations, of which a large proportion are immigrants. Much attention has been focused on the relationship between ethnicity, ethnic identity, and consumption Cherian, 1992, 1994;Venkatesh, 1995;Hui et al, 1998;Rossiter and Chan, 1998;Laroche et al, 1998;Chung and Fischer, 1999), and the impact of acculturation and assimilation on consumption practices (Webster, 1994;Lee and Tse, 1994;D'Rozario and Choudhury, 2000;Eastlich and Lotz, 2000;Laroche and Tomiuk, 2001).…”
Section: Introductionmentioning
confidence: 98%